Enduring dispositions: Examining punitive logics in the context of disciplinary reform - Brent, John J. (Theoretical criminology, 2019)
Reflecting the punitive turn in criminal justice, schools have adopted a crime control orientation when responding to student misconduct. Termed the ‘criminalization of school discipline', this trend has diminished student and school outcomes while also establishing a school-to-prison pipeline. Consequently, there has been mounting pressure to reform punitive and disproportionate practices. While research has evaluated the impact of remedial programs, little work explores how punitive logics continue to structure disciplinary responses. Drawing from ethnographic and interview data, this study examines the entrenchment of punitive dispositions in the context of appeals for alternative practices. By tracing the contours of punitive norms within a non-criminal justice context, this study captures the mechanisms through which penal logics infuse into society and extend beyond criminal justice systems.